FORMATION OF MECHANISM OF MANAGEMENT OF INNOVATIVE ACTIVITY OF HOTEL ECONOMY - ILNITSKA-GYKAVCHUK, GALINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Successful operation of the enterprise is practically impossible without innovations that allow to attract new consumers, improve product quality, competitiveness. The article considers the essence and main types of innovations in the hotel industry. Prerequisites for the introduction of innovations in the hospitality industry are: increasing competition; increasing consumer requirements; growing demand for goods and services; the desire of enterprises to increase market share, attract new customers, improve the image, technological processes of providing services, reduce costs and more. Obstacles to the introduction of innovations are identified: high cost of investment, lack of financial resources, unwillingness of management staff to innovate, high risk, lack of experience. Organizational and economic mechanism of management of innovative activity of hotel industry is a system of principles, functions, methods, tools, strategies, and also normative-legal maintenance which purpose is effective carrying out of innovative policy of the enterprise for improvement of its competitiveness in the market and quality of services. The structure of this mechanism is revealed. The principles of innovation management in the hotel industry are defined: assessment of innovation efficiency, continuity, complexity, sustainability, security, system, compliance with the needs of stakeholders. Methods of innovation management are given: economic incentives, socio-psychological and organizational-legal. The following instruments are defined: laws, regulations, loans, taxes, tax benefits, state and regional programs, plans, financing, rent, franchising and others. Each company chooses its innovation strategy depending on its capabilities. Innovative strategies of hotel management are revealed.